The Clinical and Polynucleotide Repeat Expansion Analysis of ATXN2, NOP56, AR and C9orf72 in Patients With ALS From Mainland China - Hou, Xiaorong; Li, Wanzhen; Liu, Pan; Liu, Zhen; Yuan, Yanchun; Ni, Jie; Shen, Lu; Tang, Beisha; Wang, Junling (Frontiers in Neurology, 2022)
Background Repeat expansions, including those in C9orf72 and ATXN2, have been implicated in amyotrophic lateral sclerosis (ALS). However, there have been few studies on the association of AR and NOP56 repeat expansion with ALS, especially in China. Accordingly, we aimed to evaluate the frequency of C9orf72 and ATXN2 repeat mutations and investigate whether NOP56 and AR repeat expansion are risk factors for ALS. Methods In this study, 736 ALS patients and several hundred healthy controls were recruited. Polymerase chain reaction (PCR) and repeat-primed PCR (RP-PCR) were performed to determine the repeat lengths in C9orf72, ATXN2, AR, and NOP56. Results GGGGCC repeats in C9orf72 were observed in six ALS patients (0.8%, 6/736) but not in any of the controls (0/365). The patients with pathogenic GGGGCC repeats showed shorter median survival times than those with a normal genotype (p = 0.006). Regarding ATXN2 CAG repeats, we identified that intermediate repeat lengths (29–34 copies) were associated with ALS (p = 0.033), and there was no difference in clinical characteristics between the groups with and without intermediate repeats (p > 0.05). Meanwhile, we observed that there was no association between the repeat size in AR and NOP56 and ALS (p > 0.05). Conclusions Our results demonstrated that pathogenetic repeats in C9orf72 are rare in China, while intermediate CAG repeats in ATXN2 are more frequent but have no effect on disease phenotypes; the repeat size in AR and NOP56 may not be a risk factor for ALS.